The relationship of student's use patterns and assessment of the IKIP Sanata Dharma library resources, facilities and services to library use - Arief, Bernard B. (1992)
This study attempts to analyze the relationship of student library use to the resources, facilities, and services of the IKIP Sanata Dharma Library, Yogyakarta, Indonesia, as assessed by the students. The objectives of the study are: 1) To determine the status of the IKIP Sanata Dharma Library resources, facilities, and services as evaluated by the students; 2) To find out if a relationship exists between these library resources, facilities and services and student library use; 3) To determine whether student personal factors were related to student library use.